Green synthesis of silver nanoparticles from Catharanthus roseus dried bark extract deposited on graphene oxide for effective adsorption of methylene blue dye. Issue 4 (August 2020) - Rohaizad, Aliff; Shahabuddin, Syed; Shahid, Muhammad Mehmood; Rashid, Nur Maisarah; Hir, Zul Adlan Mohd; Ramly, Mohammad Mukhlis; Awang, Khalijah; Siong, Chiu Wee; Aspanut, Zarina
Graphical abstract: Highlights: Facile and green biosynthesis of AgNPs (1–26 nm size) using Catharanthus roseus and deposited onto GO sheets. Biosynthesized AgNPs/GO exhibited outstanding adsorption of methylene blue dye. The stability of AgNPs/GO was retained within a period of 60 days. Abstract: The present work reports the facile and green synthesis of silver nanoparticles from Catharanthus Roseus ( C. Roseus ) dried barks extract doped with graphene oxide (AgNPs/GO). The deposition of silver nanoparticles onto graphene oxide sheets were confirmed by UV–vis spectrometer and X-ray diffraction analysis. The synthesized AgNPs/GO displayed high crystallinity with absorption peak at about 400 nm. TEM analysis showed that biosynthesized AgNPs are mostly in a spherical form with particles size ranging from 1 to 26 nm. The existence of functional groups such as hydroxyl, epoxy and carboxylic in GO are believed to be the reason for the anionic character of the synthesised nanocomposite. Whilst, AgNPs functions as spacers assisting the segregation of stacked GO sheets thus promoting larger surface area. The evaluation of its adsorption capacity was carried out against methylene blue (MB) dye. The addition of biosynthesized AgNPs on GO sheets synergistically envisages the best adsorption capacity at 100 mM of AgNPs with almost a complete removal of MB in less than 5 min. Based on the pseudo second-order kinetic approach, the highest adsorption rate constant of 1.4563 g mg −1  min -1 was obtained. The overall adsorption capacity was enhanced due to the presence porous nanocomposite with highly disperse AgNPs anchored onto the surface of GO sheets.